Smartphone Application for Self-Care in Type-2 Diabetes Mellitus Patients with Contextual Learning Model - Bagus Santosa, Winanda Rizki; Nisha Nambiar; Erlina Abdullah; Sheylla Septina Margaretta (HM Publisher, 2024)
Type-2 diabetes mellitus (T2DM) is an emergency problem that can cause death and disability worldwide. By using contextual learning models, smartphone applications can be an innovative solution for improving self-care and health condition management. This research aims to know the effectiveness of smartphone applications for self-care in type-2 diabetes mellitus patients with contextual learning models. Pre-test and post-test control group design was used by researchers. The study was conducted in the period October 2nd, 2023 - January 2nd, 2024. The number of samples collected using the G Power formula was 110 intervention groups and 110 control groups. To select samples, researchers used a purposive sampling method. This research involved T2DM patients treated at nine Health Centers in Kediri, Indonesia. In the smartphone application educational intervention group with the contextual learning model, there was an increase in self-care from a mean of 43,03 to 81,53, and a p-value result of 0,008 was obtained. In the control group using the booklet, there was an increase in self-care from a mean of 37,19 to 52,62, and a p-value result of 0,000 was obtained. Smartphone applications with contextual learning models are more effective in improving self-care than education using booklets; however, both types of education can improve self-care in T2DM.